2015
DOI: 10.1186/s12906-015-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of aroma-acupressure and aromatherapy for the treatment of dementia-associated agitation

Abstract: BackgroundOne of the most common symptoms observed in patients with dementia is agitation, and several non-pharmacological treatments have been used to control this symptom. However, because of limitations in research design, the benefit of non-pharmacological treatments has only been demonstrated in certain cases. The purpose of this study was to compare aroma-acupressure and aromatherapy with respect to their effects on agitation in patients with dementia.MethodsIn this experimental study, the participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 25 publications
1
95
2
1
Order By: Relevance
“…7 For example, an agitated patient can often be calmed by music, touch, and aromatherapy, especially in combination with other personalized approaches, whereas those who are hallucinating are more likely to need medication as part of the treatment plan. 7,9,[13][14][15] At times even optimally applied nonpharmacologic therapies simply do not work because of numerous factors, including disease variation and progression. 8,16 Medications used "off label" for BPSD include anxiolytics, antidepressants, cognitive enhancers, antipsychotics, and anticonvulsant mood stabilizers.…”
mentioning
confidence: 99%
“…7 For example, an agitated patient can often be calmed by music, touch, and aromatherapy, especially in combination with other personalized approaches, whereas those who are hallucinating are more likely to need medication as part of the treatment plan. 7,9,[13][14][15] At times even optimally applied nonpharmacologic therapies simply do not work because of numerous factors, including disease variation and progression. 8,16 Medications used "off label" for BPSD include anxiolytics, antidepressants, cognitive enhancers, antipsychotics, and anticonvulsant mood stabilizers.…”
mentioning
confidence: 99%
“…Aromatherapy with lavender oil in another study, however, showed improvements in agitation, the treatment made people with dementia more relaxed and that reduced the symptom. However, aromatherapy in combination with acupressure had an even greater effect [23]. Aromatherapy in combination with massage has been shown to give a significant difference in depressive symptoms in comparison to the standardized control group.…”
Section: Aromatherapymentioning
confidence: 99%
“…Regarding the symptom of agitation, aromatherapy combined with massage overall did not improve over a lengthy period, however, differences were detected within 24 hours after intervention during certain weeks of the intervention. The conclusion was that aromatherapy in combination with massage can be an effective and safe intervention for specific agitated behaviors and depression in individuals with dementia [23]. …”
Section: Aromatherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Passive and interactive music interventions were also found to cause short-term parasympathetic dominance [16]. Aroma therapy, a passive intervention, was also found effective in activating HF, tending to create a relaxed state in the elderly person [18]. Using heart rate variability (HRV) analysis, five minutes of music therapy revealed that activation of HF power.…”
Section: Introductionmentioning
confidence: 99%